1998
DOI: 10.1109/89.709672
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid mono/stereo acoustic echo canceler

Abstract: In many applications, such as teleconferencing, multimedia workstations, televideo gaming, etc., stereo sound is already, or will soon be, implemented to give spatial realism that mono systems cannot offer. In such hands-free systems, stereophonic acoustic echo cancelers are absolutely necessary for full-duplex communication. In this paper, we propose a new acoustic echo canceler (AEC) based on a fundamental experimental observation that the stereo effect is due mostly to sound energy below about 1000 Hz. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…(34) (or Eq. (35)) and (14). The stereophonic case is characterized by the strong correlation between x 1 ðnÞ and x 2 ðnÞ resulting in the appearance of two additional terms at the end of Eq.…”
Section: Article In Pressmentioning
confidence: 98%
See 3 more Smart Citations
“…(34) (or Eq. (35)) and (14). The stereophonic case is characterized by the strong correlation between x 1 ðnÞ and x 2 ðnÞ resulting in the appearance of two additional terms at the end of Eq.…”
Section: Article In Pressmentioning
confidence: 98%
“…Stereophonic teleconferencing provides more natural acoustic perception than monophonic teleconferencing [7,14]. With the ongoing prevalence of high-speed processors and the introduction of efficient low-complexity adaptive algorithms, stereophonic acoustic echo cancellation has become an achievable task those days and has been implemented successfully [9].…”
Section: A Stereophonic Fast Weighted Subband Adaptive Algorithm (Sfws)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown that the only solution to the non-uniqueness problem is to reduce the correlation between the stereo signals, and an efficient low-complexity method for this purpose was also given in [8]. Reference [10] presents a combination of mono and stereo echo cancellations, which has the benefit of lower complexity than a pure stereo solution. Lately, attention has been focused on the investigation of other methods that decrease the cross-correlation between the channels in order to get well-behaved estimates of the echo paths [11].…”
Section: Introductionmentioning
confidence: 99%